The Metabolically Active Bacterial Microbiome of Tonsils and Mandibular Lymph Nodes of Slaughter Pigs - Mann, Evelyne; Pinior, Beate; Wetzels, Stefanie U.; Metzler-Zebeli, Barbara U.; Wagner, Martin; Schmitz-Esser, Stephan (Frontiers in Microbiology, 2015)
The exploration of microbiomes in lymphatic organs is relevant for basic and applied research into explaining microbial translocation processes and understanding cross-contamination during slaughter. This study aimed to investigate whether metabolically active bacteria (MAB) could be detected within tonsils and mandibular lymph nodes (MLNs) of pigs. The hypervariable V1-V2 region of the bacterial 16S rRNA genes was amplified from cDNA from tonsils and MLNs of eight clinically healthy slaughter pigs. Pyrosequencing yielded 82,857 quality-controlled sequences, clustering into 576 operational taxonomic units (OTUs), which were assigned to 230 genera and 16 phyla. The actual number of detected OTUs per sample varied highly (23-171 OTUs). Prevotella zoogleoformans and Serratia proteamaculans (best type strain hits) were most abundant (10.6% and 41.8% respectively) in tonsils and MLNs, respectively. To explore bacterial correlation patterns between samples of each tissue, pairwise Spearman correlations (rs) were calculated. In total, 194 strong positive and negative correlations |rs| ≥ 0.6 were found. We conclude that (i) lymphatic organs harbor a high diversity of metabolically active bacteria, (ii) the occurrence of viable bacteria in lymph nodes is not restricted to pathological processes and (iii) lymphatic tissues may serve as a contamination source in pig slaughterhouses. This study confirms the necessity of the EFSA regulation with regard to a meat inspection based on visual examinations to foster a minimization of microbial contamination.